ACTUAL METHODS' OF DIAGNOSIS AND TREATMENT ARVI - A. N. Kupchenko; Zh. B. Ponezheva (SINAPS LLC, 2016)
The classification of respiratory viruses and etiological structure in coldly epidemiological period of year 2014 in article, clinical features and differential - diagnostics simptoms of influenza and other acute respiratory infections are presented in detail, modern methods of diagnosis and treatment of influenza and ARVI described, therapeutic and prophylactic doses of drugs for etiological and pathogenesis therapy, the basic directions of specific and nonspecific immunization and preventive vaccination presented in article.